Research on the Impact of Coastal Land Reclamation on Geomorphic Complexity and Tidal Energy Dissipation—A Case Study of Zhoushan Islands, Hangzhou Bay - Shixia Zhang; Qiankun Hong; Huifang Guo (Engineering Reports)
ABSTRACT Coastal mudflats are vital land resources. In recent years, coastal reclamation has emerged as a vital strategy for alleviating coastal land supply shortages and for developing marine resources in coastal areas. However, large‐scale coastal reclamation changes the natural landscape properties of sea areas, triggering alterations in the surrounding hydrodynamic and ecological environments. Despite the significant impact of coastal geomorphic features on tidal energy loss and disaster prevention, few studies have explored the intrinsic connection between the complexity of coastal landscapes and the rate of tidal reduction. This relationship is crucial for predicting potential tidal energy loss responses to large‐scale changes in geomorphologic features caused by accelerating coastal land reclamation. This study focuses on Hangzhou Bay as the research area and develops a model that combines the correlation between the rate of tidal reduction and the complexity of coastal landscapes. The model is constructed using fractal geometry theory and quantitative methods, while also incorporating principles from ocean dynamics theory. The model is applied to assess the impacts of reclaimed land on the geomorphic complexity and tidal energy dissipation in the Zhoushan Islands. Results indicate a high correlation between differential tide reduction rates and coastal geomorphic complexity. Application of this model reveals that traditional reclamation planning and design substantially alter coastal morphology. Consequently, the significant reduction in the fractal dimension (D) and shape index (S) leads to a tidal reduction rate decrease of over 88%, posing substantial threats to coastal and estuarine bay disaster prevention and ecosystem services. The study proposes effective control indicators and scientific reclamation planning measures, providing a theoretical basis and novel methods for the rational utilization and sustainable development of coastal mudflat resources.